Effects of SO2 on Cu-SSZ-39 catalyst for the selective catalytic reduction of NOx with NH3. Issue 5 (21st January 2020) - Du, Jinpeng; Shi, Xiaoyan; Shan, Yulong; Xu, Guangyan; Sun, Yu; Wang, Yingjie; Yu, Yunbo; Shan, Wenpo; He, Hong
Abstract : The impact of SO2 on Cu-SSZ-39 was firstly investigated, and sulfation mechanism at different temperature was proposed. Abstract : In this work, the Cu-SSZ-39 catalyst was sulfated at different temperatures (200 °C, 400 °C or 600 °C) in the presence of water to investigate the effects of sulfation on its catalytic performance in NH3 -SCR. Sulfation at 200 °C and 400 °C resulted in a significant decrease in NO x conversion at low temperatures, while sulfation at 600 °C showed only slight effect on the SCR activity of Cu-SSZ-39. The coverage of active sites by H2 SO4 was the main reason for the deactivation of the catalyst sulfated at 200 °C and 400 °C, while the formation of stable CuSO4 species should also be responsible for the catalytic activity loss of the catalysts sulfated at 200 °C, 400 °C and 600 °C. After regeneration at 600 °C, the activities of the sulfated catalysts could be recovered partially but were still lower than those of the fresh catalysts, due to the formation of stable sulfated Cu species.